Hydrophilic modified polyphenylene sulfide fabric diaphragm and preparation method thereof
Through the method of swelling-induced amphiphilic polymer chimerization, the polyphenylene sulfide fabric separator is modified to solve the problem of insufficient hydrophilicity, realize an efficient electrolysis process, extend the service life of the separator, and maintain stable performance in a high-temperature alkaline environment.
Patent Information
- Application Number
- CN202510314802.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-18
AI Technical Summary
The existing polyphenylene sulfide (PPS) fabric separators are insufficiently hydrophilic during alkaline water electrolysis, resulting in large internal resistance of the electrolytic cell, low electrolytic efficiency and safety hazards. The modification method has problems such as damage to fibers, uneven modification and major impacts caused by environmental conditions.
By swelling inducing amphiphilic polymer chimerization, the polyphenylene sulfide fabric separator is modified, and the spontaneous orientation of the amphiphilic polymer is used to insert the hydrophobic chain segments into the fibers, and the hydrophilic chain segments are exposed to the fiber surface to enhance the hydrophilic properties of the separator.
It effectively improves the hydrophilicity of the PPS fabric diaphragm, reduces the internal resistance of the electrolytic cell, improves the electrolytic efficiency, extends the service life of the diaphragm, and maintains stable performance in a high-temperature alkaline environment.
Smart Images

Figure CN119843491A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of materials, and in particular relates to a hydrophilic modified polyphenylene sulfide fabric diaphragm and a preparation method thereof. Background Art
[0002] In today's energy field, water electrolysis hydrogen production technology has attracted much attention for its sustainability. It mainly includes four technical categories: alkaline water electrolysis (ALK), proton exchange membrane electrolysis (PEM), high-temperature solid oxide electrolysis (SOEC) and solid polymer anion exchange membrane electrolysis (AEM). Among them, the working principle of ALK is to use electrical energy to decompose water in an alkaline electrolyte environment to produce hydrogen and oxygen. ALK uses relatively cheap non-precious metals (such as iron, cobalt, nickel, etc.) as catalysts, while avoiding the use of expensive titanium-based components, and has greater potential in cost control. Therefore, the large-scale development of alkaline water electrolysis hydrogen production technology is of great strategic significance for reducing the cost of large-scale hydrogen production, and can provide strong support for future energy transformation and sustainable development.
[0003] In the whole alkaline water electrolysis process, the diaphragm is the key factor to ensure the efficient and safe operation of the whole electrolysis process. Therefore, the alkaline water electrolysis diaphragm has become an important technical branch in the alkaline water electrolysis hydrogen production technology. The main role of the diaphragm in the electrolysis process is reflected in the following aspects: 1. The diaphragm can clearly separate the positive and negative poles of the electrolytic cell to form independent cathode and anode chambers, prevent the short circuit caused by direct contact between the two poles, ensure that the electrolysis reaction can proceed in an orderly manner according to the predetermined path, and provide a stable space environment for the separate generation of hydrogen and oxygen; 2. The diaphragm needs to effectively prevent hydrogen and oxygen from permeating each other, ensure the safety and reliability of the electrolysis process and the production environment, and prevent the mixing of hydrogen and oxygen generated by electrolysis and cause potential safety risks; 3. The diaphragm needs to have a high porosity while ensuring airtightness, so that hydroxide ions can be smoothly transferred from the cathode to the anode. These pores are like "fast channels" tailored for ions, allowing hydroxide ions to move freely through them, greatly reducing the resistance in the ion transmission process, thereby ensuring the continuous and stable progress of the electrolysis reaction and improving the efficiency of the entire electrolysis process.
[0004] It can be seen that for alkaline water electrolysis diaphragm materials, it needs to meet a series of strict and multi-dimensional requirements such as high porosity, high gas barrier properties, high hydrophilicity, high corrosion resistance, high mechanical strength, low resistivity and dimensional stability, in order to adapt to the complex working conditions and high performance requirements in the alkaline water electrolysis hydrogen production process.
[0005] In the development history of alkaline water electrolysis diaphragm materials, asbestos diaphragms meet most of the above requirements and were widely used as early commercial alkaline diaphragm materials. However, with the continuous advancement of science and technology and people's increasing attention to health and environmental issues, asbestos has been gradually eliminated from the market due to its serious hazard of carcinogenicity. In order to find a suitable substitute, researchers have found that polyphenylene sulfide (PPS), a high-performance engineering material, has many excellent properties, making it an ideal choice to replace asbestos after a lot of research and exploration.
[0006] The main chain of PPS is composed of alternating benzene rings and sulfur atoms. The introduction of benzene rings makes its molecular chain have a certain rigidity; the molecular chain with symmetrical structure and regular distribution can be partially condensed into a crystalline state. These structures give PPS excellent high temperature resistance, good mechanical strength, excellent thermal stability, outstanding chemical corrosion resistance, antioxidant and other properties, enabling it to stably exist in the harsh environment of alkaline electrolysis water and become a rising star in the field of alkaline water electrolysis diaphragms.
[0007] However, despite the many advantages of PPS, its weak hydrophilicity gradually becomes prominent when it is used in alkaline water electrolysis diaphragms. Due to insufficient hydrophilicity, using only PPS fabric as an alkaline water electrolysis diaphragm will result in excessive internal resistance of the electrolyzer. This is because it is difficult for water molecules to fully diffuse and penetrate on the hydrophobic PPS surface, which hinders the transmission of ions at the interface between the diaphragm and the electrolyte, thereby increasing the energy loss in the electrolysis process and reducing the electrolysis efficiency; at the same time, the insufficient hydrophilicity of PPS will also lead to insufficient binding ability with water molecules, thereby causing a decrease in its air tightness and bringing safety hazards. Therefore, in order to improve the application performance of PPS fabric in alkaline water electrolysis hydrogen production, improving its hydrophilicity has become the focus and key direction of current research. At present, common surface modification methods include: coating treatment, chemical oxidation treatment, plasma treatment, irradiation grafting treatment and corona discharge treatment.
[0008] For example, the Chinese invention patent with application number CN202410599971.6 discloses a polyphenylene sulfide fiber composite NH2-UiO 66 The diaphragm and preparation method thereof are prepared by adding NH2-UiO into the polyphenylene sulfide fiber diaphragm after sulfonation treatment. 66 The composite solution is subjected to a hydrothermal reaction to obtain the polyphenylene sulfide fiber composite NH2-UiO 66 The method can effectively improve the hydrophilicity of polyphenylene sulfide fiber. However, in the patent, the hydrophilic NH2-UiO 66 The sulfonic acid group reacts with the sulfonic acid group to form a sulfonamide bond fixed on the fiber surface, and the sulfonic acid group itself will gradually be reacted with the base, eventually resulting in NH2-UiO 66Gradually falling off from the substrate surface, the hydrophilicity will also decrease. At the same time, the hydrothermal reaction temperature in the preparation process is 120°C, which is too high and may destroy the crystalline part of the PPS fiber, resulting in a decrease in mechanical properties.
[0009] The Chinese invention patent with application number CN202410087625.X discloses a method for preparing a PPS diaphragm for hydrophilic electrolysis of water, wherein zirconium oxide and polyphenylene sulfide are mixed and melt-spun to obtain a surface diaphragm, and then polyphenylene sulfide and aramid material are mixed and melt-spun to obtain a core membrane, and the surface diaphragm is sandwiched with the core membrane for hot calendering to obtain a composite diaphragm, and then a hydroentanglement process is performed to obtain a PPS diaphragm for hydrophilic electrolysis of water. However, in the patent method, the physical blending process of PPS resin and zirconium oxide inorganic nanoparticles is prone to problems of poor fusion and phase separation, which ultimately leads to uneven hydrophilicity on the surface of the PPS diaphragm.
[0010] The Chinese invention patent with application number CN202011524159.5 discloses a polyphenylene sulfide fabric for a water electrolyzer, which is sulfonated by using sulfuric acid and chromic acid; wherein chromic acid can decompose the polyphenylene sulfide macromolecular segments into small molecular segments, and concentrated sulfuric acid can enter the interior of PPS for sulfonation, thereby introducing hydrophilic sulfoxide groups on the surface and inside of the PPS fiber, and allowing it to be used for a long time, thereby improving the stability and life of the PPS diaphragm. However, in the patented method, the strongly oxidizing chromic acid decomposes the polyphenylene sulfide macromolecular segments into several small molecular segments, which will change the original physical and chemical properties of PPS and reduce the mechanical strength of the PPS diaphragm; and the internal sulfoxide functional groups still need to be exposed to alkali solution to exert their hydrophilic effect, which means that the internal functional groups will also be corroded by the alkali solution over time.
[0011] It can be seen that the above-mentioned modification methods have problems such as damage to fibers, uneven modification and being greatly affected by environmental conditions; in addition, the introduced hydrophilic groups cannot ensure whether they have lasting hydrophilicity, whether they can withstand the harsh electrolysis conditions of high temperature and alkalinity, and whether the mechanical properties meet the standards, which ultimately leads to limited improvement in the overall hydrophilicity.
[0012] In the existing PPS fabric hydrophilic modification technology, there are problems such as being unable to be used for a long time in a high-temperature alkaline environment and damaging the mechanical properties of the diaphragm itself, resulting in a shortened service life of the diaphragm. Summary of the invention
[0013] In view of this, the present invention aims to overcome the defects in the prior art and proposes a hydrophilic modified polyphenylene sulfide fabric diaphragm and a preparation method thereof.
[0014] To achieve the above object, the technical solution of the present invention is achieved as follows: A method for preparing a hydrophilic modified polyphenylene sulfide fabric diaphragm comprises the following steps: Step 1 is to add a brominated alkane, polyoxyethylene diamine and a strong base into a container, add a solvent into the container under a nitrogen flow, heat the container, cool to room temperature after the reaction is completed, add the obtained polymer solution into hydrochloric acid for precipitation, soak the obtained precipitate in anhydrous ethanol, wash with deionized water, and dry to obtain a triblock amphiphilic polymer; Step 2 is to use the mixed solution to wash the polyphenylene sulfide fabric diaphragm, and then dry it for standby use; Step 3 is to perform swelling treatment on the polyphenylene sulfide fabric diaphragm treated in step 2, add the triblock amphiphilic polymer obtained in step 1 thereto, perform primary drying, secondary orientation arrangement and secondary drying after the reaction is completed, and obtain the hydrophilically modified polyphenylene sulfide fabric diaphragm.
[0015] Furthermore, the mass ratio of the brominated alkane, polyoxyethylene diamine and strong base in step 1 is 1:0.78:0.25-0.35; and the strong base is K2CO3.
[0016] Furthermore, the temperature of the heating step in step 1 is 50-100° C., and the reaction time is 12-24 hours.
[0017] Furthermore, the brominated alkane in step 1 is at least one of 1-bromohexadecane, 1-bromooctadecane, 1-bromoeicosane or 1-bromodocosane; and the solvent in step 1 is DMAC and / or toluene.
[0018] Furthermore, the molecular weight of the polyoxyethylene diamine in step 1 is 500-5000; and the concentration of the hydrochloric acid is 0.05-0.5 mol / L.
[0019] Furthermore, the mixed solution in step 2 is a mixture of at least two of deionized water, ethanol or acetone.
[0020] Furthermore, the thickness of the polyphenylene sulfide fabric diaphragm in step 2 is 0.7-1.0 mm, and the weight is 450-550 g / m 2 , the diameter of polyphenylene sulfide fiber is 8-18 μm.
[0021] Furthermore, the swelling agent in the swelling step of step 3 is 3,3'-dichlorobiphenyl and petroleum ether in a mass ratio of 7-9:1-3; the addition amount of the triblock amphiphilic polymer in step 3 is 0.5-5% of the mass of the polyphenylene sulfide fabric diaphragm.
[0022] Furthermore, the swelling step in step 3 is oil bath heating at a temperature of 80-150°C for 12-24 hours; the primary drying step in step 3 is performed at a temperature of 50-100°C for 4-12 hours.
[0023] A hydrophilic modified polyphenylene sulfide fabric diaphragm prepared by using the preparation method.
[0024] The reaction process in step 1 is shown in formula (I):
[0025] Formula (I) Among them, the hydrophobic part is selected from a polyethylene segment with small steric hindrance, and its precursor is a brominated alkane (m=16, 18, 20, 22); the hydrophilic part is selected from a polyether polymer with good alkali resistance, and its precursor is polyoxyethylene diamine (molecular weight is 1000).
[0026] The alkyl segments on both sides of the triblock amphiphilic polymer in step 1 and the PPS main chain are both oil-soluble structures. According to the principle of like dissolves like, the alkyl segments are more likely to enter between the PPS molecular chains; while the aminoalkoxy segments in the middle of the amphiphilic polymer are water-soluble segments, which repel the PPS molecular chains, allowing them to be exposed outside the PPS molecular chains, thereby providing hydrophilicity to the PPS.
[0027] After the surface of the PPS fabric is swollen by the swelling agent in step 3, the swelling agent can penetrate into the surface and interior of the PPS fiber. Under the action of the swelling agent, the intermolecular forces between the molecular chains in the amorphous region of the PPS fiber are weakened, the PPS molecular chains begin to disentangle, and the gaps between the molecular chains become larger; this provides enough space for the hydrophobic segments at both ends of the amphiphilic polymer PE-NH-PEO-NH-PE to enter the interior of the PPS. 3,3'-dichlorobiphenyl, as the main swelling agent, can penetrate into the interior of the PPS, weaken the van der Waals forces between the molecular chains in the amorphous region of the PPS, and make it easier for petroleum ether to enter and further swell the PPS. According to the principle of like dissolves like, the hydrophobic segments at both ends of PE-NH-PEO-NH-PE have a closer structure to petroleum ether. With the help of petroleum ether, the hydrophobic segments will approach the polymer surface and gradually insert into the gaps created by the swelling of the molecular chains in the amorphous region of the PPS fiber. At the same time, the hydrophilic segments in the middle of the amphiphilic polymer are insoluble in 3,3'-dichlorobiphenyl and petroleum ether. Therefore, under the repulsive effect of the two swelling agents, the hydrophobic segments will further move between the PSS molecular chains, providing a driving force for the hydrophobic segments to enter the gaps between the molecular chains in the amorphous region of PPS.
[0028] As the swelling agent evaporates and is removed, the molecular chains in the amorphous region of PPS are released from swelling. Under the action of van der Waals forces, the PPS molecular chains approach each other again and entangle with each other. In this process, the hydrophobic segments of PE-NH-PEO-NH-PE are firmly fixed and embedded between the PPS molecular chains.
[0029] The hydrophilic segments in PE-NH-PEO-NH-PE were reoriented and arranged by soaking in anhydrous ethanol, and the residual un-embedded amphiphilic polymers were removed. Finally, the hydrophilic-modified PPS alkaline water electrolysis membrane was obtained after washing with deionized water and drying.
[0030] Compared with the prior art, the present invention has the following advantages: The preparation method of the hydrophilic modified polyphenylene sulfide fabric diaphragm described in the present invention improves the hydrophilicity of the polyphenylene sulfide fabric diaphragm by inducing the intercalation of amphiphilic polymers through swelling. This method can effectively improve the hydrophilicity of the PPS fabric diaphragm without damaging the mechanical properties of the PPS fabric, and reduce its internal resistance in the electrolytic cell application scenario; and can continue to play a role in the long-term electrolysis of water, greatly extending its service life, and can meet the needs of industrial production. The preparation method of the hydrophilic modified polyphenylene sulfide fabric diaphragm described in the present invention is simple to operate, has obvious modification effect, is not affected by environmental conditions, does not affect the mechanical properties of PPS itself, and retains hydrophilic properties for a long time; and has broad application prospects in other high-performance fiber surface modification fields.
[0031] The hydrophilic modified polyphenylene sulfide fabric diaphragm described in the present invention utilizes a swelling agent to swell the amorphous region of the fiber surface, and simultaneously adds an amphiphilic polymer, and utilizes the spontaneous orientation of the amphiphilic polymer to make the hydrophobic chain segment tend to be inserted into the fiber. At the same time, the entanglement between the PPS molecular chains provides a strong anchoring force for the embedding of the hydrophobic chain segment of the amphiphilic polymer, thereby exposing the hydrophilic chain segment on the fiber surface, thereby increasing the hydrophilic property of the PPS fabric. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The scanning electron microscope images of the PPS fabric separator embedded with the amphiphilic polymer described in the embodiment of the present invention are shown in FIG. A, where FIG. B is the original PPS fabric separator, and FIG. A is the embedded PPS fabric separator; Figure 2 This is an optical physical picture of the chimeric amphiphilic polymer PPS fabric diaphragm at the moment of dripping water as described in an embodiment of the present invention: wherein, Figure A is the original PPS fabric diaphragm, and Figure B is the chimeric PPS fabric diaphragm. DETAILED DESCRIPTION
[0033] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0034] Example 1
[0035] A method for preparing a hydrophilic modified polyphenylene sulfide fabric diaphragm comprises the following steps: (1) 10 g of bromodocosane, 7.8 g of polyoxyethylene diamine and 3.5 g of K2CO3 were added to a 500 mL three-necked round-bottom flask, and then 133.5 g of DMAC and 44.5 g of toluene were added as solvents under a nitrogen flow. The above reagent mixture was heated to 70°C and reacted for 24 hours. After cooling to room temperature, the polymerization was stopped, and the polymer solution was precipitated in 0.1 mol / L hydrochloric acid. The precipitated polymer was thoroughly washed with water and ethanol and dried to constant weight; (2) The PPS fabric sheet was first ultrasonically washed in anhydrous ethanol for 0.5 h, then ultrasonically washed in deionized water for 0.5 h, and then dried for use; (3) The PPS fabric dried in step (1) was immersed in a swelling agent (the mass ratio of petroleum ether to 3,3'-dichlorobiphenyl was 1:9), 1.5 g of the amphiphilic polymer PE-NH-PEO-NH-PE was added, and then heated in an oil bath at 100°C for 12 h; (4) taking the PPS fabric in step (3) out of the swelling agent, lightly wiping off the excess swelling agent on the surface, and then vacuum drying at 60°C and -0.1 MPa; (5) The PPS fabric dried in step (4) is immersed in anhydrous ethanol for 5 minutes, washed with deionized water, and dried to obtain a hydrophilically modified PPS fabric membrane.
[0036] Example 2
[0037] The only difference from Example 1 is that the brominated alkane is 1-bromooctadecane.
[0038] Example 3
[0039] The only difference from Example 1 is that the swelling temperature is 60°C.
[0040] Comparative Example 1 The only difference from Example 1 is that the polymer is PE-COO-PEG-COO-PE.
[0041] Comparative Example 2 The only difference from Example 1 is that the polymer is polystyrene-block-poly(ethylene-ran-butylene)-block-polystyrene-graft-maleic anhydride, CAS No. 124578-11-6.
[0042] Comparative Example 3 The only difference from Example 1 is that the swelling agent is petroleum ether.
[0043] Comparative Example 4 The only difference from Example 1 is that the swelling agent is 3,3'-dichlorobiphenyl.
[0044] Comparative Example 5 The only difference from Example 1 is that the swelling agent is dimethyl sulfoxide.
[0045] The PPS diaphragms of the above embodiments and comparative examples were subjected to performance tests, and the test items and methods were as follows: Characterization of microscopic morphology changes: Scanning electron microscopy (SEM) was used to characterize the morphology of the PPS separator before and after modification.
[0046] Surface resistance: The test is carried out according to the test standard of the electronic industry standard SJ / T 10171.5-1991 of the People's Republic of China for the surface resistance of alkaline battery separators.
[0047] Water diffusion time: The water absorption rate and water absorption time before and after hydrophilic treatment are tested according to GB / T 21655.1-2008 standard.
[0048] Alkaline electrolytic water resistance test: The PPS fabric separators of the above examples and comparative examples were immersed in a 30 wt% KOH solution at 90°C for 360 h, and then the surface resistance and drip diffusion time were tested. The results are shown in Table 1 below.
[0049] Table 1 Test data
[0050] like Figure 1 As shown in Figure 2, it can be seen that the surface roughness of the PPS fabric fiber embedded with PE-NH-PEO-NH-PE is significantly increased; Figure 2 As shown in the figure, it can be seen that the water contact angle of the PPS fabric membrane embedded with PE-NH-PEO-NH-PE is significantly smaller than that of the PPS fabric membrane without PE-NH-PEO-NH-PE, indicating that PE-NH-PEO-NH-PE significantly improves the hydrophilicity of PPS.
[0051] As shown in Table 1, from the comparison between Examples 1 and 2, it can be seen that the length of the hydrophobic segment has little effect on the entry of the amphiphilic polymer into the interior of PPS, and the surface resistance and the hydrophilic time are at the same level; from the comparison between Examples 1 and 3, it can be seen that the temperature has a greater effect on the swelling degree of PPS. When the temperature of Example 1 is significantly higher than that of Example 3, the swelling degree of PPS in Example 1 is higher than that of Example 3, so that the amphiphilic polymer in Example 1 can be more embedded between the PPS molecular chains, so that its hydrophilic effect is the best.
[0052] By comparing Comparative Example 1 with Example 1, it can be seen that the surface resistance of the diaphragm in Comparative Example 1 is significantly increased after alkali boiling, which indicates that the amphiphilic polymer in Comparative Example 1 is almost completely destroyed under the action of strong alkali and cannot tolerate strong alkali.
[0053] By comparing Comparative Example 2 with Example 1, it can be seen that the hydrophilic effect of the diaphragm in Comparative Example 1 is not obvious, but the mechanical properties of the two are at the same level, which shows that the swelling degrees of the two are at the same level, but the hydrophobic chain segment of the amphiphilic polymer in Comparative Example 2 has too large a steric hindrance and cannot enter between the molecular chains of PPS. Therefore, the hydrophilic ability of the diaphragm in Comparative Example 2 is not significantly improved.
[0054] By comparing Comparative Examples 3-4 with Example 1, it can be seen that the membrane surface resistance and hydrophilic time in Comparative Examples 3 and 4 are not as good as those in Example 1, which shows that the effect of mixed use of swelling agents is worse than that of using swelling agents alone, which can better increase the swelling degree of PPS and enable more amphiphilic polymers to enter between PPS molecular chains, bringing better hydrophilic effect.
[0055] By comparing Comparative Example 5 with Example 3, it can be seen that the mechanical properties of the two diaphragms are similar, but the swelling temperature in Comparative Example 5 is 100°C, which means that the dimethyl sulfoxide in Comparative Example 5 is not a good swelling agent for PPS, and the amphiphilic polymer cannot enter PPS; therefore, the hydrophilic time and surface resistance of the diaphragm in Comparative Example 5 are close to those in Example 3, and the hydrophilic effect of the diaphragm is not good.
[0056] After the amphiphilic polymer PE-NH-PEO-NH-PE is embedded in the surface of the hydrophilic modified PPS fabric membrane of the present invention, the hydrophilic property of the PPS membrane is significantly improved, the surface resistance thereof is effectively reduced, and the hydrophilic property thereof can still stably exist in a high-temperature alkaline electrolyte environment for a long time; however, the hydrophilic modified PPS membrane of the comparative example has the problem of insufficient hydrophilic modification, which leads to serious energy loss and affects production efficiency.
[0057] The present invention modifies the surface of the PPS diaphragm by inducing the amphiphilic polymer to enter the interior of the PPS by swelling the PPS fiber and fixing it by embedding: the hydrophobic segments at both ends of the PE-NH-PEO-NH-PE are spontaneously inserted into the interior of the swollen PPS fiber under the action of interfacial tension, while the hydrophilic segments can be retained on the fiber surface; this part can enhance the interaction ability between the PPS fiber surface and water molecules, and the water molecules can be more evenly distributed on the fiber surface to form a continuous hydration layer, thereby achieving the improvement of the hydrophilicity of the PPS fabric. The appearance of the hydrophilic layer improves the transmission environment of the hydroxide ions in the alkaline water electrolysis diaphragm, making it easier for the hydroxide ions to migrate in the diaphragm, reducing the resistance and energy loss in the hydroxide transmission process, thereby greatly reducing the diaphragm resistance and greatly improving the energy utilization efficiency.
[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a hydrophilic modified polyphenylene sulfide fabric diaphragm, characterized in that: The steps include: Step 1 is to add a brominated alkane, polyoxyethylene diamine and a strong base into a container, add a solvent into the container under a nitrogen flow, heat the container, cool to room temperature after the reaction is completed, add the obtained polymer solution into hydrochloric acid for precipitation, soak the obtained precipitate in anhydrous ethanol, wash with deionized water, and dry to obtain a triblock amphiphilic polymer; Step 2 is to use the mixed solution to wash the polyphenylene sulfide fabric diaphragm, and then dry it for standby use; Step 3 is to perform swelling treatment on the polyphenylene sulfide fabric diaphragm treated in step 2, add the triblock amphiphilic polymer obtained in step 1 thereto, perform primary drying, secondary orientation arrangement and secondary drying after the reaction is completed, and obtain the hydrophilically modified polyphenylene sulfide fabric diaphragm.
2. The method for preparing the hydrophilic modified polyphenylene sulfide fabric diaphragm according to claim 1, characterized in that: The mass ratio of the brominated alkane, polyoxyethylene diamine and strong base in step 1 is 1:0.78:0.25-0.35; the strong base is K2CO3.
3. The method for preparing the hydrophilic modified polyphenylene sulfide fabric diaphragm according to claim 1, characterized in that: The temperature of the heating step in step 1 is 50-100° C., and the reaction time is 12-24 hours.
4. The method for preparing the hydrophilic modified polyphenylene sulfide fabric diaphragm according to claim 1, characterized in that: The brominated alkane in step 1 is at least one of 1-bromohexadecane, 1-bromooctadecane, 1-bromoeicosane or 1-bromodocosane; and the solvent in step 1 is DMAC and / or toluene.
5. The method for preparing the hydrophilic modified polyphenylene sulfide fabric diaphragm according to claim 1, characterized in that: The molecular weight of the polyoxyethylene diamine in step 1 is 500-5000; the concentration of the hydrochloric acid is 0.05-0.5 mol / L.
6. The method for preparing the hydrophilic modified polyphenylene sulfide fabric diaphragm according to claim 1, characterized in that: The mixed solution in step 2 is a mixture of at least two of deionized water, ethanol or acetone.
7. The method for preparing the hydrophilic modified polyphenylene sulfide fabric diaphragm according to claim 1, characterized in that: The polyphenylene sulfide fabric diaphragm in step 2 has a thickness of 0.7-1.0 mm and a gram weight of 450-550 g / m 2 , the diameter of polyphenylene sulfide fiber is 8-18 μm.
8. The method for preparing the hydrophilic modified polyphenylene sulfide fabric diaphragm according to claim 1, characterized in that: The swelling agent in the swelling step of step 3 is 3,3'-dichlorobiphenyl and petroleum ether in a mass ratio of 7-9:1-3; the addition amount of the triblock amphiphilic polymer in step 3 is 0.5-5% of the mass of the polyphenylene sulfide fabric diaphragm.
9. The method for preparing the hydrophilic modified polyphenylene sulfide fabric diaphragm according to claim 1, characterized in that: The swelling step of step 3 is oil bath heating at a temperature of 80-150°C for 12-24 hours; the primary drying step of step 3 is 4-12 hours at a temperature of 50-100°C.
10. A hydrophilic modified polyphenylene sulfide fabric diaphragm prepared by the preparation method according to claim 1.
Citation Information
Patent Citations
A polyphenylene sulfide fabric for water electrolyzers, its preparation method and uses
CN113201839B
A preparation method of pps diaphragm for hydrophilic water electrolysis
CN118223072B
Polyphenylene sulfide fiber composite NH2-UIO66 diaphragm and preparation method thereof
CN118441317A
Method for hydrophilic modification of polypropylene porous membrane surface by using amphipathic molecule
CN101011645A
Diaphragm, method for preparing diaphragm and secondary battery comprising diaphragm
CN105789538A
Cited By
Modified preparation method of polyphenylene sulfide composite diaphragm and application of polyphenylene sulfide composite diaphragm in alkaline electrolytic cell
CN122382657A